Estrategias de Afrontamiento de Modelos Webcam de la Ciudad de Bogotá y su Relación con el Bienestar (2022)
The present degree work was carried out with the objective of identifying the coping strategies of webcam models in the city of Bogotá and their relationship with well-being through an in-depth interview and in which problems experienced before being webcam models were identified. and currently exercising this work, as well as the meanings attributed to these experiences, this research was developed with a qualitative methodology, from the theoretical model of Lazarus and Folkman.